ASSESSING THE TYPES, CONDITION AND FUNCTIONALITY OF WATER, SANITATION AND HYGIENE FACILITIES IN PUBLIC PRIMARY SCHOOLS IN THE ZABZUGU DISTRICT OF GHANA - Tiswin, T. N.; Luguterah, A.; Aladago, A. D. (UDS International Journal of Development, 2019)
This study assessed the types, condition and functionality of water, sanitation and hygiene facilities in public primary schools in the Zabzugu District of the Northern Region of Ghana. This cross-sectional descriptive survey was carried out in February 2015. Twenty-five schools were randomly selected for the study. The results showed that the main WASH facilities in the schools were hand-pump boreholes, covered plastic containers, Kumasi Ventilated Improved Pit latrines, flat-concrete floor urinals, and veronica buckets. The condition of water infrastructure was good in 36% of the schools, satisfactory in 48% of the schools and bad in 16% of the schools. The sanitation infrastructure was good in 28% of the schools, satisfactory in 42% of the schools and bad in 31% of the schools. Handwashing facilities which, were the only hygiene facilities the schools were good in 91% of schools and bad in 9% of schools. Additionally, the available water infrastructure was functional in 42% of the schools, partially-functional in another 42% of the schools and non-functional in 16% of the schools. Sanitation facilities were functional in 85% of the schools, partially-functional in 12.5% of the schools and non-functional in just 2.5% of schools. The study concludes that whereas the available handwashing facilities were underutilised, there was a shortfall of WASH infrastructure in most of the public primary schools in the Zabzugu, including disability-friendly toilets, urinals and menstrual hygiene management facilities. The study recommends that the Ghana Education Service and the Ministry of Education support the schools to improve their infrastructure and intensify education on WASH to ensure usage of the facilities. Keywords: Wash, Schools, Children, Ghana, Health